Model Sistem Manajemen Riset - Sik Sumaedi; Fatimah Zulfah; Tri Widianti; Medi Yarmen (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2015)
Research institution has an important role in enhancing a nation’s competitiveness. Hence, research institution should have a good performance; relevant to the need of increasing competitiveness. Related to this, a research management system appropriate for research institution was needed. Unfortunately, until now, the aforementioned research management system model remained unclear. This research aimed to formulate a research management system for research center under LIPI (Indonesian Institute of Sciences). Research management system model was formulated based on the analysis of three standards (SNI ISO/ IEC 17025:2008, ISO 9001: 2008, and KNAPPP 02), LIPI characteristics analysis, and the practices of the existing management system. The result showed that generally, the developed research management system FRQVLVWHGRI¿YHVFRSHV quality management systems, management responsibility, resource management, realization of research products or service, and monitoring and evaluation.